Changes in antigenic profile during culture of Neoparamoeba sp., causative agent of amoebic gill disease in Atlantic salmon - Villavedra, M; McCarthy, K; To, J; Morrison, R; Crosbie, P; Broady, K; Raison, RL (2005)
Amoebic gill disease (AGD), the most serious infectious disease affecting farmed salmon in Tasmania, is caused by free-living marine amoeba Neoparamoeba sp. The parasites on the gills induce proliferation of epithelial cells initiating a hyperplastic response and reducing the surface area available for gaseous exchange. AGD can be induced in salmon by exposure to freshly isolated Neoparamoeba from AGD infected fish, however cultured Neoparamoeba are non-infective. We describe here antigenic differences between freshly isolated and in vitro cultured parasites, and within individual isolates of the parasite cultured under different conditions. Immunoblot analysis using polyclonal antisera, revealed differences in the antigen profiles of two cultured isolates of Neoparamoeba sp. when they were grown on agar versus in liquid medium. However, the antigen profiles of the two isolates were very similar when they were grown under the same culture conditions. Comparison of these antigen profiles with a preparation from parasites freshly isolated from infected gills revealed a very limited number of shared antigens. In addition monoclonal antibodies (mAbs) raised against surface antigens of cultured parasites were used in an indirect immunofluorescence assay to assess the expression of specific surface antigens of Neoparamoeba sp. after various periods in culture. Significant changes in antigen expression of freshly isolated parasites were observed after 15 days of in vitro culture. The use of mAb demonstrated progressive exposure/expression of individual antigens on the surface of the freshly isolated parasites during the period in culture. © 2005 Australian Society for Parasitology Inc. Published by Elsevier Ltd. All rights reserved.